THE DISTRIBUTING SYSTEM OF SEA RECLAMATION AS AN INHERITANCE IN PULAU BUNGIN VILLAGE: AN ISLAMIC LAW PERSPECTIVE - Siti Aminah; Arif Sugitanata (IAIN Ambon, 2022)
AbstractThe purpose of this research is to examine the division system of sea reclamation as an inheritance in Pulau Bungin Village, West Nusa Tenggara, based on the standpoint of Islamic law. The qualitative research method was used in this study. The observation, interview, and documentation provided in the form of induction analysis through reduction, discussion, and conclusion are data collection methods. It starts with a family who is free to claim the sea area around the house as their property, which will then be passed on to the testator's heirs after the testator's death. Following the claim, a marker or stake is placed as evidence that someone already owns the area. The next step is to legitimise the related-vil.Keywords: Reclamation, Inheritance, Pulau Bungin, Islamic Law.